2017
DOI: 10.1016/j.vaccine.2017.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Varicella seroepidemiology in United States air force recruits: A retrospective cohort study comparing immunogenicity of varicella vaccination and natural infection

Abstract: seroepidemiology in United States air force recruits: A retrospective cohort study comparing immunogenicity of varicella vaccination and natural infection" (2017 a b s t r a c tBackground/Objectives: Infection with varicella zoster virus (VZV) produces lifelong immunity, but duration of post-vaccination immunity has not been established. The purpose of this study is to determine if a difference exists in the long-term seropositivity of anti-VZV antibodies in a cohort of young adults who were vaccinated agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…It has been previously reported that when the varicella vaccine was given to children with renal insufficiency pre‐transplant, combined with immunosuppressive treatment after transplantation, it induced less persistent antibody levels in comparison with historically reported values in healthy vaccinated children . In a study published in 2017, the VZV infection was demonstrated to produce lifelong immunity in healthy individuals, whereas seropositivity after VZV vaccination was estimated to decrease by 8% for each year that had elapsed since vaccination . Broyer et al studied paediatric renal transplant candidates who were seropositive after the natural varicella infection and found that they lost VZV antibodies after grafting: 0.4% after one year, 2.8% after two years and 4.5% after five years .…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that when the varicella vaccine was given to children with renal insufficiency pre‐transplant, combined with immunosuppressive treatment after transplantation, it induced less persistent antibody levels in comparison with historically reported values in healthy vaccinated children . In a study published in 2017, the VZV infection was demonstrated to produce lifelong immunity in healthy individuals, whereas seropositivity after VZV vaccination was estimated to decrease by 8% for each year that had elapsed since vaccination . Broyer et al studied paediatric renal transplant candidates who were seropositive after the natural varicella infection and found that they lost VZV antibodies after grafting: 0.4% after one year, 2.8% after two years and 4.5% after five years .…”
Section: Discussionmentioning
confidence: 99%
“…We consider this to be the most important reason for the increased odds of being hospitalized for children with underlying disease. That the proportion of children with complications was not higher in children with underlying medical conditions could be an indication of the effectiveness of antiviral 644 (30) 296 (28) 395 (25) 359 (21) 138 (19) 1832 (26) Outpatients (no. cases/annual incidence/100 000)…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Chickenpox vaccination parameters, such as those associated with primary vaccine failure and waning of vaccination immunity were derived from literature. [32][33][34] We built the mechanism whereby PeerJ reviewing PDF | (2017:08:19793:4:0:NEW 4 May 2018)…”
Section: Parameterizationmentioning
confidence: 99%